Hubungan Antara Pola Asuh Otoritatif dengan Kesejahteraan Psikologis pada Siswa/I SMA Global Prima Medan - Vicky Firmansyah Siagian; Novlyncia Novlyncia; Jesslyn Wijaya; Haposan Lumbantoruan; Rianda Elvinawanty; Hasanuddin Hasanuddin (Mahesa Research Center, 2023)
The paper was conducted to determine whether there is a correlation between authoritative parenting and psychological well-being in Global Prima National Plus Medan high school students. The hypothesis in this study is that there is a positive correlation between authoritative parenting and psychological wellbeing. The research subject used in this study were 260 students from SMA Global PrimaNational Plus Medan and used a proportionate stratified random sampling technique. This research uses quantitative methodes; data was collected using an authoritative parenting scale of 30 items and a psychological well-being scale of 42. The assumption test and linearity rest. The data were examined using the Pearson Prodcut Moment correlation test through the SPSS version 21.0 for the Windows program. The results of data analysis found a positive correlation between authorirative parenting and psychological wll-being in Global Prima National Plus Medan high school students with a Person Product Moment correlation coefficient of 0.466 and sig. worth 0.000(p<0.05). The results showed that the authoritative parenting variable contributed to psychological well-being by 21.4%, and the remaining 78.6% was influenced by other factors not examined. The results of this study concluded that the research hypothesis stating a positive correlation between authoritative parenting and psychological well-being could be accepted.